A perspective on the current use of the phase distribution model for predicting milk‐to‐plasma drug concentration ratio. (1st October 2022) - Zhang, Mian; Sychterz, Caroline; Chang, Ming; Huang, Lu; Schmidt, Brian J.; Gaohua, Lu
Abstract: The phase distribution model, proposed by Atkinson and Begg in 1990, has been widely used for predicting breastmilk‐to‐plasma drug concentration ratio. However, misrepresentations of the equations have been noted in recent publications. In this perspective, we revisit the derivation of the equations and provide an R/Shiny interface for the model with a view to helping scientists in this field acquire in‐depth understanding of the theoretical background and implementation of the model.